The Internet As an Educational and Communicative Environment for Student Youth - Agalarova, Karina; Sorokina, Hanna; Uhrimova, Iryna; Kozlova, Olena; Sutula, Oksana; Turuta, Olena (Akademické sdružení MAGNANIMITAS, Czech Republic, 2022)
In modern society today, there is the process of general informatization, which is due to the action of certain “information trends”. The leading place in this process is occupied by the emergence and functioning of the global Internet. The rapid development of the global computer network Internet affects various areas of human life and activity. The Internet attracts the active research interest of humanities scientists: sociologists, psychologists, political scientists, economists, lawyers, philosophers. One should note a fairly wide range of humanitarian and scientific problems in the study of the Internet. The relevance of the chosen topic is associated with the rapid development of the Internet and its introduction into various spheres of human life, primarily as a means of mass communication, used, in particular, in the educational and communicative environment. The purpose of the study is to determine the features of the use of Internet channels for the formation and development of educational and communicative environment of student youth.
Keywords: educational environment; Internet; learning; smart education